Evaluating Public Sector Efficiency And Its Influence On Economic Development Across Nations - Hawwin Muzakki; M. Munif (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Public sector efficiency plays a critical role in determining the quality of public services and fostering sustainable economic development. This study aims to evaluate the relationship between public sector efficiency and economic development across nations through a library research approach. Drawing upon a comprehensive review of academic literature, policy reports from international organizations such as the World Bank, IMF, and OECD, and previous empirical studies, this research synthesizes key findings on how efficient governance contributes to economic growth, human development, and poverty reduction. The results indicate that countries with higher levels of public sector efficiency tend to exhibit better development outcomes, including more effective service delivery, improved budget allocation, and inclusive growth. Furthermore, strong institutional capacity, fiscal transparency, and accountable governance are consistently associated with positive development performance. The study concludes that enhancing public sector efficiency through bureaucratic reform, digital innovation, and institutional strengthening is essential to achieving sustainable development goals. These findings offer valuable insights for policymakers and scholars seeking to formulate governance-based strategies for national and global development.